The Relationship Between The Mother's Level Of Knowledge About Nutritious Food And The Nutritional Status Of Toddlers In Pancuran Bambu Village, Sambas District, Sibolga City 2019 - Agustianny Situmeang; Friska A. Sihombing (Institute of Computer Science (IOCS), 2019)
Improving the quality of independent human resources needs to be supported by a balanced nutritional state which must be supported by the availability of sufficient food at a price that is stable and affordable by the purchasing power of the general public. The results of the national census survey revealed that the percentage of news that was nutritious for workers was 70.88% in 2012 and in 2013 it fell to 69.59%. Toddlers with less or bad teeth by 25.82% in the same year with an increase to 28.17% in the following year. The purpose of the study was to determine the relationship between the mother's level of knowledge about nutritious food and the nutritional status of children under five in the Pancuran Bamboo sub-district, Sambas sub-district, Sibolga city in 2018. This type of research was go relative with a sample of 62 respondents. Sampling was carried out by collecting data on all patients who came to the Pancuran Bambu sub-district, Sambas Selatan sub-district, Sibolga in 2018. Based on the results, it is known that the respondents' knowledge about nutritious food for toddlers is 52 people (83.9%) good knowledgeable and the minority has less knowledge 4 people (6.5%). Characteristics of respondents it is known that the age of the majority of respondents aged 27-31 years as many as 46 people (74.2%), it is known that the education of the majority of respondents has a high school education as many as 39 people (62.9%), and the type of work of the majority of respondents work as entrepreneurs, namely as many as 38 people (61.3%). The conclusion of this study is that there is a relationship between mother's knowledge about nutritious food and the nutritional status of toddlers in Pancuran Bambu Village, Sambas District, Sibolga City in 2018 because P <0.05 (p = 0.00) and r count > r table (r count = 0.650> r table = 0.244. It is necessary to increase nutritional knowledge through intensive and continuous counseling activities carried out through Posyandu activities, social gathering, or religious activities.